CREATIVE THINKING AND COLLABORATIVE ABILITY OF ELEMENTARY STUDENTS WITH THE IMPLEMENTATION OF THE STEM INTEGRATED PROJECT-BASED LEARNING MODEL - Ai Herlina; Sri Dewi Nirmala; Ucu Rahayu (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2023)
This paper is motivated by the author's efforts to improve the quality of Human Resources (HR) in accordance with the demands/developments of the times. This research was conducted to (1) find out how the differences in creative and collaborative thinking skills through STEM-integrated project-based learning and the use of conventional learning models, (2) describe creative and collaborative thinking skills using STEM-integrated project-based learning models. This study uses a quantitative approach method. It was held at Gugus 4 Cibadak, Public Elementary School Pamuruyan (as the control class) and Public Elementary School Cilengo (as the experimental class). Creative thinking data collection is using posttest and pretest, while for collaborative ability data collection is by observation sheets. The results showed that (1) the creative thinking ability (mean pretest 32,14 for experiment class and 40,17 for control class, mean posttest 79, 29 for experiment class and 40,83 for control class) and collaborative ability of the class with STEM-integrated project-based learning were superior/got more significant results than the class that used conventional learning models, (2) students' creative abilities emerged into several indicators such as fluency, flexibility, original thinking, and elaborative thinking, (3) collaborative abilities appear in the field based on indicators of confidence, positive attitude, respect, giving encouragement, and building group spirit.